(untitled) (Journal of Creative Industry and Sustainable Culture, 2022)
Nowadays, people are busy with gadgets, social media and playing video games that tends their bodies to physically inactive. However, Virtual Reality (VR) exergaming in literature has proven to be one of the best solutions to encourage these sedentary people to live in a healthier lifestyle. Exergaming refers to a combination of video games with a physical exercise that rely on the technology that can track body movement. Hence, this project aims to develop a cycling exergame that integrate with HTC Vive hand controller in VR. There are four phases have been carried out namely (i) problem investigation, (ii) designing the game structure, (iii) implementation of VR cycling exergame, and (iv) testing and evaluation. The usability testing results shows the users feedback on the development of VR Exergame for cycling in terms of the user interface design, player interaction, difficulty of the game and user satisfaction in understanding the game. The user acceptance testing results shows that this game works accordingly, however there are some suggestion and expectation from user that can be measured for improvement and enhancement in future works. Based on the result, this project is successfully produced a cycling exergame in VR and significantly improve the user experience in VR.